Comprehensive Evaluation for Protective Coatings: Optical, Electrical, Photoelectrochemical, and Spectroscopic Characterizations - Shen, Xin; Yanagi, Rito; Solanki, Devan; Su, Haoqing; Li, Zhaohan; Xiang, Cheng-Xiang; Hu, Shu (Frontiers in Energy Research, 2022)
Numerous efficient semiconductors suffer from instability in aqueous electrolytes. Strategies utilizing protective coatings have thus been developed to protect these photoabsorbers against corrosion while synergistically improving charge separation and reaction kinetics. Recently, various photoelectrochemical (PEC) protective coatings have been reported with suitable electronic properties to ensure low charge transport loss and reveal the fundamental photoabsorber efficiency. However, protocols for studying the critical figures of merit for protective coatings have yet to be established. For this reason, we propose four criteria for evaluating the performance of a protective coating for photoelectrochemical (PEC) water-splitting: stability, conductivity, optical transparency, and energetic matching. We then propose a flow chart that summarizes the recommended testing protocols for quantifying these four performance metrics. In particular, we lay out the stepwise testing protocols to evaluate the energetics matching the coating at a semiconductor/coating/(catalyst)/liquid interface. Finally, we provide an outlook for the future benchmarking needs for coatings.